New Ventilator Strategies: High-Frequency Oscillatory Ventilation Combined with Volume Guarantee - Sánchez-Luna, M.; González-Pacheco, N.; Belik, J.; Santos, M.; Tendillo, F. (American Journal of Perinatology, 2018)
High-frequency oscillatory ventilation (HFOV) has been proposed as an alternative method of invasive ventilation in immature infants to prevent ventilator lung injury. To better control the size of the high-frequency tidal volume and to prevent large tidal volumes, a new strategy of controlling the tidal volume during HFOV (VThf) has been developed, HFOV–volume guarantee (VG). Data from preclinical, neonatal animal studies in normal and surfactant-depleted lungs have demonstrated the feasibility of this technique to directly control the VThf in the normal compliance and low compliance situations. Different I:E ratios also can modify the effect of CO2 washout during HFOV combined with VG in a different way as without the VG modality. Finally, clinical use of this technique in newborn infants has demonstrated the possibility of using very high frequency combined with constant very low VThf to decrease the risk of lung trauma related to the ventilator.
Keywords: high-frequency oscillatory ventilation; volume guarantee ventilation; gas exchange; newborn ventilation; respiratory distress syndrome